Qandeel-e-adab qawaid-o-insha class 2 - Maqsood, Syed (Asian publishers Lahore, 2014)
"Qandeel-e-Adab: Qawaid-o-Insha" is an Urdu textbook that focuses on the rules of grammar, literary forms, and techniques of writing in Urdu. It aims to equip students with the skills necessary for effective communication and creative expression in the language.